Academic Senate Minutes 2011-09-01 - Academic Senate:::::::::
Crash Course in Robert's Rules. Membership changes to the Senate Diversity Subcommittee first reading waived and approved. Constitutional Change: Structure of Chairship of the Faculty – First Reading completed. Resolution Regarding Opposition to Proposed Changes in Presidential Searches – first reading waived and approved. Faculty Eligible for Emeritus Status approved.